Implementation of Character Education Values in Indonesian Language Learning - Selva Istiqomah; Suhirman Suhirman; Heny Friantary (Yayasan Karinosseff Muda Indonesia, 2023)
This study aims to explain (1) the implementation of character education values in Indonesian language learning at MAN 2 Bengkulu City (2) explain the supporting and inhibiting factors for the implementation of character education values in Indonesian language learning at MAN 2 Bengkulu City. The type of research is qualitative research. Data collection techniques are observation, interview, and document analysis. Data validity technique is triangulation method. Data analysis technique is Miles and Huberman model: data collection, data reduction, data presentation, and conclusion. The results concluded that MAN 2 Bengkulu City had implemented the value of character education at the planning, implementation, and assessment stages. In planning, Indonesian language teachers have included the value of character education in the lesson plan. The overall implementation of MAN 2 Bengkulu City has implemented 14 character education values in Indonesian language learning. In the assessment carried out by Indonesian language subject teachers, it is found in the lesson plan which not only assesses in terms of academics. However, it also assesses non-academic aspects such as assessing student attitudes. Supporting factors for the implementation of character education values in Indonesian language learning are lesson plans that include character education values. The inhibiting factors for the implementation of character education values in Indonesian language learning are student behavior and not yet having a language laboratory.